Human alpha-adducin gene, blood pressure, and sodium metabolism - Kamitani, A; Wong, Z Y; Fraser, R; Davies, D L; Connor, J M; Foy, C J; Watt, G C; Harrap, S B (Hypertension (Dallas, Tex. 1979), 1998)
The adducin genes contribute significantly to population variation in rat blood pressure and cell membrane sodium transport. The 460Trp mutation of the human alpha-adducin gene has been associated with hypertension, in particular hypertension sensitive to sodium restriction. We studied the relationship between the 460Trp mutation and population variation in blood pressure and sodium metabolism. From 603 Scottish families, we selected 151 offspring and 224 parents with blood pressures in either the upper (high) or bottom (low) 30% of the population distribution and measured the 460Trp mutation using allele-specific hybridization. In offspring, we also measured exchangeable sodium, plasma volume, and total body water. Plasma levels of components of the renin-angiotensin system, atrial natriuretic peptide, and cellular sodium and transmembrane sodium efflux were also estimated. The overall frequency of the 460Trp mutation was 27.1%. In offspring and parent groups, we found no difference in the genotype or allele frequencies of the 460Trp mutation between subjects with high or low blood pressure. There was no overall association between the alpha-adducin genotypes and blood pressure variation. In offspring, the 460Trp mutation was not associated with any significant differences in body fluid volumes or exchangeable sodium; levels of plasma renin, angiotensin II, aldosterone, or atrial natriuretic peptide; intracellular sodium; or ouabain-sensitive transmembrane sodium efflux. These findings suggest that in our Scottish population, the alpha-adducin 460Trp polymorphism is not related to blood pressure and does not affect whole body or cellular sodium metabolism.